2023
DOI: 10.1021/jacs.3c07186
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Oxidized Polyethylene Enables Access to Functional Polyethylenes with Greater Reuse

Jake X. Shi,
Nicodemo R. Ciccia,
Subhajit Pal
et al.

Abstract: Polyethylene is a commodity material that is widely used because of its low cost and valuable properties. However, the lack of functional groups in polyethylene limits its use in applications that include adhesives, gas barriers, and plastic blends. The inertness of polyethylene makes it difficult to install groups that would enhance its properties and enable programmed chemical decomposition. To overcome these deficiencies, the installation of pendent functional groups that imbue polyethylene with enhanced pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Yet even using just 0.5% peroxide loading in air showed oxygenated moieties ( M19 ), indicating that these functional groups arise from the presence of air. Some studies have shown that oxygenated functional groups can enhance the polymer properties, 68 yet here, the presence of oxygenated moieties in M19 clearly decreases the viscosity profiles, providing further support that the enhanced viscosity profiles are due to the presence of long chain branching.…”
Section: Resultssupporting
confidence: 80%
“…Yet even using just 0.5% peroxide loading in air showed oxygenated moieties ( M19 ), indicating that these functional groups arise from the presence of air. Some studies have shown that oxygenated functional groups can enhance the polymer properties, 68 yet here, the presence of oxygenated moieties in M19 clearly decreases the viscosity profiles, providing further support that the enhanced viscosity profiles are due to the presence of long chain branching.…”
Section: Resultssupporting
confidence: 80%
“…These postpolymerization reactions, however, can suffer from drawbacks such as uncontrolled chain cleavage and selectivity, if promoted in a free-radical fashion. , Substantial efforts led to the development of more controlled, transition-metal catalyzed C–H functionalization. The introduction of keto and hydroxyl groups via this method can enhance materials properties, for example, enabling better adhesion to polar surfaces . Despite significant advances, the functional group selectivity remains a main challenge for postpolymerization modification of polyethylenes, and usually mixtures of ketones and hydroxyl groups are obtained from Ni- or Ru-catalyzed C–H functionalization. , The synthesis of exclusively keto-containing polymers via this pathway was also reported but requires an additional oxidation step of such mixed “oxo-polyethylenes” by Cp*Ir-catalyzed transfer dehydrogenation using acetone as oxidant . Even though a high selectivity for keto groups (>99%) can be achieved initially with Cu catalysts and benzaldehyde as a reagent, the C–H oxidation results in a significant molecular weight decrease vs the original material .…”
Section: Synthesismentioning
confidence: 99%
“…This advancement facilitates programmed chemical decomposition. 6 Depending on the desired qualities of the final product, polyethylene is manufactured at high pressures and temperatures in the presence of any one of a number of catalysts. Depending on the synthesis technique, other structures (leading to long and short branches) may be present.…”
Section: Introductionmentioning
confidence: 99%
“…This process produces monofunctional variants with bulk properties surpassing those of unmodified polyethylene. This advancement facilitates programmed chemical decomposition . Depending on the desired qualities of the final product, polyethylene is manufactured at high pressures and temperatures in the presence of any one of a number of catalysts.…”
Section: Introductionmentioning
confidence: 99%